Rationale and Methodology of the 2018 Canadian Armed Forces Members and Veterans Mental Health Follow-up Survey (CAFVMHS): A 16-year Follow-up Survey: Raison D'être Et Méthodologie De L'enquête De Suivi Sur La Santé Mentale Des Membres Des Forces Armées Canadiennes Et Des Anciens Combattants, 2018 (ESSMFACM). (November 2021) - Afifi, Tracie O.; Bolton, Shay-Lee; Mota, Natalie; Marrie, Ruth Ann; Stein, Murray B.; Enns, Murray W.; El-Gabalawy, Renée; Bernstein, Charles N.; Mackenzie, Corey; VanTil, Linda; MacLean, Mary Beth; Wang, Jian Li; et al.
Objective: Knowledge is limited regarding the longitudinal course and predictors of mental health problems, suicide, and physical health outcomes among military and veterans. Statistics Canada, in collaboration with researchers at the University of Manitoba and an international team, conducted the Canadian Armed Forces Members and Veterans Mental Health Follow-Up Survey (CAFVMHS). Herein, we describe the rationale and methods of this important survey. Method: The CAFVMHS is a longitudinal survey design with 2 time points (2002 and 2018). Regular Force military personnel who participated in the first Canadian Community Health Survey Cycle 1.2—Mental Health and Well-Being, Canadian Forces Supplement (CCHS-CFS) in 2002 ( N = 5, 155) were reinterviewed in 2018 ( n = 2, 941). The World Mental Health Survey–Composite International Diagnostic Interview was used with the Diagnostic and Statistical Manual of Mental Disorders, fourth edition ( DSM -IV) criteria. Results: The CAFVMHS includes 2, 941 respondents (66% veterans; 34% active duty) and includes data on mental disorder diagnoses, physical health conditions, substance use, medication use, general health, mental health services, perceived need for care, social support, moral injury, deployment experiences, stress, physical activity, military-related sexual assault, childhood experiences, and military and sociodemographic information. Conclusions: The CAFVMHS provides a unique opportunity to further understand the health and well-being of military personnel in Canada over time to inform intervention and prevention strategies and improve outcomes. The data are available through the Statistics Canada Research Data Centres across Canada and can be used cross-sectionally or be longitudinally linked to the 2002 CCHS-CFS data.